PEMBERIAN PENGUATAN DAN BELAJAR MANDIRI TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN MELAKUKAN PROSEDUR ADMINISTRASI - Novitasari, Lia (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2013)
ABSTRACT The objectives of this research are to investigate whether or not there is a significant effects of: (1) the administration of reinforcement on the learning achievement in the subject matter of Conducting the Administration Procedures; (2) the independent learning on the learning achievement in the subject matter of Conducting the Administration Procedures; and (3) the administration reinforcement and the independent learning simultaneously on the learning achievement in the subject matter of Conducting the Administration Procedures. This research used the descriptive quantitative method. The population of the research was all of the students as many as 86 in Grade X of the Office Administration Skill Program of Vocational High School Batik 2 of Surakarta in Academic Year 2012/2013. The samples of the research were 60% of the population or 51 students, and were taken by using the proportional random sampling technique. The data of the research were gathered through questionnaire and documentation. They were then analyzed by using the statistical test with the correlation and multiple regression technique of analysis. The results of the research are as follows: (1) there is a significant effect of the administration of reinforcement on the learning achievement in the subject matter of Conducting the Administration Procedures of the students in Grade X of the Office Administration Skill Program of Vocational High School Batik 2 of Surakarta in Academic Year 2012/2013 as indicated by the value of rcount = 0.468 > rtable = 0.276 at the significance level of 5%; (2) there is a significant effect of the independent learning on the learning achievement in the subject matter of Conducting the Administration Procedures of the students in Grade X of the Office Administration Skill Program of Vocational High School Batik 2 of Surakarta in Academic Year 2012/2013 as shown by the value of rcount = 0.525 > rtable = 0.276 at the significance level of 5%; and (3) there is a simultaneously significant effect of the administration reinforcement and the independent learning on the learning achievement in the subject matter of Conducting the Administration Procedures of the students in Grade X of the Office Administration Skill Program of Vocational High School Batik 2 of Surakarta in Academic Year 2012/2013 as pointed out by the value of Fcount = 20.195 > rtable = 3.191 at the significance level of 5%. In Addition, the other finding of the research is ? = 27.581 + 0.322 X1 + 0.489 X2, meaning that on average the learning achievement in the subject matter of Conducting the Administration Procedures will increase or decrease as much as 0.489 for each unit of increase or decrease in the independent learning. The relative contribution of the administration of reinforcement toward the learning achievement is as much as 43.82%, and that of the independent learning toward the learning achievement is as much as 56.18%. In addition, the effective contribution of the administration of reinforcement toward the learning achievement is as much as 20.02%, and that of the independent learning toward the learning achievement is much as 25.68%. Keywords: The administration of reinforcement, independent learning, and learning achievement.